The Effectiveness of English Language Courseware on School students learning Motivation - hashemyolia, shayesteh; Mohd Ayub, Ahmad Fauzi B (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Integration of language courseware has been wildly practiced in teaching and learning foreign language. The purpose of this study was to determine the effects of Rosetta stones English Language Courseware (RSELC) on third grade students motivation in five dimensions (intrinsic, extrinsic, self-efficacy, relevance, and anxiety) in public secondary school in Iran. This study utilized a quasi-experimental method using only post-test design which consists of two groups. Control group was taught using traditional instruction and experimental group was taught using educational software, namely RSELC. Both groups consist of 31Iranin secondary school students. In addition, A quantitative analyses revealed that there was significant difference between the groups on the overall motivation in favour of experimental group. Based on obtained results, the current study concluded RSELC that was an effective tool for teaching and learning English language at the third grade secondary school in Iran.